The educational gap paradox in the right to education for all: reflections on the Brazilian historical heritage. (Reflection and Critique Law Magazine, 2024)
This article aims to bring observations about the right to education in the country, briefly covering different historical periods, such as colonial Brazil, empire, republic, military dictatorship and the present. Through this approach, the objective is to understand the changes and continuities in the legislative development related to education throughout history, with the aim of identifying gaps in educational laws and State guidelines added to the existence of an administrative obstacle. This situation generates a mismatch between legislation on education and the State's role in promoting educational collectivity, because, even if it seeks to provide universal education, it ends up evolving in an illusory way, that is, it seems to exist in an idealized way, however, in practice it is not fully due to limitations and shortcomings in implementation. These legislative changes in the right to education throughout history are extremely important for discussion, considering its social conversion, since the existence of a deficit of public policies that promote competitive equality in education is remarkable, which represents an elitist bias. rooted in the education system.